Emotional Campaigning in Politics: Being Moved and Anger in Political Ads Motivate to Support Candidate and Party - Grüning, David J.; Schubert, Thomas W. (Frontiers in Psychology, 2022)
Political advertising to recruit the support of voters is an inherent part of politics. Today, ads are distributed via television and online, including social media. This type of advertisement attempts to recruit support by presenting convincing arguments and evoking various emotions about the candidate, opponents, and policy proposals. We discuss recent arguments and evidence that a specific social emotion, namely the concept kama muta, plays a role in political advertisements. In vernacular language, kama muta is typically labeled as being moved or touched. We compare kama muta and anger theoretically and discuss how they can influence voters’ willingness to support a candidate. We then, for the first time, compare kama muta and anger empirically in the same study. Specifically, we showed American participants short political ads during the 2018 U.S. midterm election campaigns. All participants saw both kama muta- and anger-evoking ads from both Democratic or Republican candidates. In total, everybody watched eight ads. We assessed participants' degree of being moved and angered by the videos and their motivation for three types of political support: ideational, financial, and personal. The emotional impact of an ad depended on its perceived source: Participants felt especially angry after watching the anger-evoking ads and especially moved by moving ads if they identified with the political party that had produced the video. Both emotions mediated were associated with increased intentions to provide support. Importantly, if one of the two emotions was evoked, its effect on political support was enhanced if participants identified with the party that had produced the ad. We discuss limitations of the method and implications of the results for future research and practice.